Surgeon eye lens dose monitoring in interventional neuroradiology, cardiovascular and radiology procedures. (December 2022) - Busoni, S.; Bruzzi, M.; Giomi, S.; Poggiali, C.; Quattrocchi, M.; Betti, M.; D'Urso, D.; Fedeli, L.; Mazzoni, L.N.; Paolucci, M.; Rossi, F.; Taddeucci, A.; et al.
Highlights: Surgeon eye lens dose measured in eight different interventional procedure types. Dosemeters read by an iSO-17025 accredited service. Median eye lens Hp (3) range, with ceiling shield: 20–60 μSv per single procedure. CT-guided lung biopsy median eye lens Hp (3): 150μSv per single procedure. Hp (3)/KAP shows a statistically significant dependency on the surgeon's height. Abstract: Purpose: This study investigated the radiation dose to surgeon eye lens for single procedure and normalised to exposure parameters for eight selected neuroradiology, cardiovascular and radiology interventional procedures. Methods: The procedures investigated were diagnostic study, Arteriovenous Malformations treatment (AVM) and aneurysm embolization for neuroradiology procedures, Coronary Angiography and Percutaneous Transluminal Coronary Angioplasty (CA-PTCA), Pacemaker and Implantable Cardioverter-Defibrillator implantation (PM-ICD), Endovascular Aortic Repair (EVAR) and Fenestrated Endovascular Aortic Repair (FEVAR) for cardiovascular and electrophysiology procedures. CT-guided lung biopsy was also monitored. All procedures were performed with table-mounted and ceiling-suspended shields (0.5 mm lead equivalent thickness), except for FEVAR and PM-ICD where only a table mounted shield was present, and CT-guided lung biopsy where no shield was used. Dose assessment was performed using a dosemeter positioned close to the most exposed eye of the surgeon, outside the protective eyewear. Results: The surgeon most exposed eye lens median Hp (3) equivalent dose for a single procedure, without protective eyewear contribution, was 18 μSv for neuroradiology diagnostic study, 62 μSv for AVM, 38 μSv for aneurysm embolization, 33 μSv for CA-PTCA, 39 μSv for PM-ICD, 49 μSv for EVAR, 2500 μSv for FEVAR, 153 μSv for CT-guided lung biopsy. Conclusions: In interventional procedures, the 20 mSv/year dose limit for surgeon eye lens exposure might be exceeded if shields or protective eyewear are not used. Surgeon eye lens doses, normalised to single procedures and to exposure parameters, are a valuable tool for determining appropriate radiation protection measures and dedicated eye lens dosemeter assignment.